Peer-led behavioural intervention to prevent cigarette and water pipe use among public high school children in Sanandaj, Iran - Mohammadi, Mahtab (2016)
Tobacco use among adolescents is one of the major public health concerns worldwide. In Iran, about 3.0 percent and 26.6 percent of adolescents aged 13 to 15 currently smoke cigarette and water pipe, respectively. The increase in adolescent’s tobacco use and subsequent health, social and economic impact associated with smoking reveals a need for more effective and empirically prevention strategies. The objective of this study was to develop, implement and evaluate the effectiveness of a peer-led behavioural intervention programme to prevent cigarette smoking and water pipe use among public high schoolchildren. A cluster randomized controlled trial design was used in this study. Out of 37 public high schools in Sanandaj City, 4 male and 4 female public high schools were randomly selected and allocated into intervention or control group. All students in grade one to three (corresponding to 14-17 years old) in selected schools were included. Data were collected using three sections questionnaire. A self-administered validated questionnaire was used to measure smoking behaviour, intention to cigarette and water pipe use and determinant factors related to cigarette and water pipe use of respondents. It was administered at baseline and 6 month post-intervention. Four-hour integrated tobacco prevention program comprising of four structured modules was developed and delivered to the intervention group by trained peer educator. Data were analyzed using IBM SPSS Statistics 21. Chi-square analyses and independent sample t-tests were used to test group equivalence between intervention and control group at baseline for categorical and continues data, respectively. Generalized estimating equations (GEE) were applied to assess the effectiveness of the intervention. Cohen’s d effect size (ES) and the odds ratio (OR) was used to interpret the results. The outcome measures were assessed at baseline and 6 months post-intervention. Data were collected from 1807 public high schoolchildren aged 14 to 17 years old. 949 participants randomized to the intervention and 934 participants to the control group. Results were based on controlling for cluster effects of schools and demographic factors. The results showed that there was significant decrease in intention to cigarette smoking (p=<0.001) and water pipe use (p=<0.001) observed after intervention. The intervention module was also effective in improving smoking knowledge (p=<0.001), normative believes with regard to perceived prevalence of cigarette smoking (p=<0.001), normative believes with regard to perceived prevalence of water pipe use (p=<0.001), self-esteem (p=<0.001) and refusal skill (p=0.035), but not for attitude toward smoking (p=0.307) and assertiveness skill (p=0.496) in intervention group six months post intervention. However, the peer-led cigarette and water pipe use prevention program used in this study, had no significant effect on smoking cigarette (p=0.264) and water pipe use (p=0.232) six months post intervention. In conclusion, peer-led behavioural intervention program developed in this study was effective to decrease the intention to cigarette and water pipe use. It was also effective in improving knowledge, normative believes with regard to perceived prevalence of cigarette and water pipe use, self-esteem and refusal skill. However, module developed, was not effective to reduce cigarette and water pipe use at 6 months post intervention among high schoolchildren in Sanandaj, Iran.